Pregnancy is associated with a reduction in the pattern of the cytotoxic activity displayed by lymphokine-activated killer cells - Salméron, O J; Vaquer, S; Salmerón, I; Moltó, L; Lapeña, P; Manzano, L; de las Heros, J I; Alvarez-Mon, M (American journal of reproductive immunology (1989), 1991)
Several modifications in the homeostasis of the maternal immune system have been implicated in the survival of the fetoplacental graft. We have investigated the adaptive response of the cytotoxic nonmajor histocompatibility complex (MHC)-restricted effector lymphocytes in pregnancy, and have found that the spontaneous lytic activity against both natural killer (NK)-sensitive and NK-resistant target cells is either decreased or lacking in peripheral blood mononuclear cells (PBMNC) from pregnant women. Recombinant interleukin-2 (rIL-2) normalizes the cytotoxic activity of PBMNC from pregnant women against NK-sensitive target cells in a dose- and time-dependent manner, without modification in the normal amounts of HNK-1+, CD16+ (Leu 11, or CD11b+ (OKM-1) present in these effector populations. However, the pattern of lytic activity against NK-resistant target cells found in PBMNC from pregnant women after short- and long-term incubation with rIL-2 was reduced in comparison with that observed in PBMNC from nongravid women in similar conditions. Moreover, rIL-2 incubation of PBMNC from pregnant subjects was not associated with an enhancement of the lytic binding against NK-resistant target cells. These findings demonstrate that pregnancy is not only associated with a reduction in the NK lytic activity of PBMNC, but also with a reduction in the generation of lymphokine-activated killer activity, in terms of the pattern of lytic activity developed.